Preparation method of super-hydrophilic antifouling coating for light component
By preparing ultra-hydrophilic anti-fouling coating, the problem of traditional coating adhesion on lightweight components is solved, better adhesion and anti-static properties are achieved, the service life of the coating is extended, and the light transmittance of the components is improved and weather resistance.
Patent Information
- Application Number
- CN202411776633.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-05
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2044-12-05
AI Technical Summary
The prior art cannot effectively prepare an ultra-hydrophilic anti-fouling coating combined with the front plate of the lightweight assembly, resulting in the inability to adhere to the traditional nanocoat, affecting the light transmittance and service life of the assembly.
The organic silicone plasma is treated with the acrylic monomer and peroxide, and then combined with the silane coupling agent and the nano SiO2 dispersion, and the antistatic agent, leveling wetting agent and surfactant are added to form a super-philic Water-resistant coating, prepared by solvent replacement method, is applied to the surface of lightweight components.
It achieves good adhesion between the ultra-hydrophilic anti-fouling coating and lightweight components, isolates pollutants, improves antistatic properties and weather resistance, and extends the service life of the coating.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention belongs to the field of lightweight components, and in particular relates to a method for preparing a super-hydrophilic antifouling coating for a lightweight component. Background Art
[0002] Due to the advantage of their own weight, lightweight components have been widely used in scenarios such as industrial and commercial roofs, solar RV power generation, balcony photovoltaics, agricultural photovoltaics, etc. where various glass components are too heavy and cannot bear the load.
[0003] Lightweight components, like traditional glass components, are mostly used in unprotected outdoor scenes. Various types of dust such as dust, dirt, and water vapor in nature will accumulate on the surface of the components for a long time, causing the surface to accumulate dust and become rough, greatly affecting the light transmittance of the components, thereby affecting the power generation, and even forming a hot spot effect, reducing the service life of the components. In addition, the accumulated dust will also cause the annual cleaning cost of the components to rise sharply, increasing the cost of the components in disguise. At present, some targeted measures have been developed for glass components on the market. Chinese patent application CN202211170066.6 has applied for the preparation of a self-cleaning, dust-free nano-coating with excellent antistatic properties, which can achieve the advantages of dust-free, reducing the frequency of cleaning, and increasing power generation. Chinese patent application CN202211654350.0 has applied for the preparation of an anti-reflection and anti-transmittance coating liquid, which is applied to the surface of photovoltaic glass to reduce reflection, increase light transmittance, and has a certain anti-fouling effect.
[0004] Although a variety of nano-coating technologies have been developed on the market to improve this problem for traditional glass components, nano-silicon coatings can only bond to inorganic-inorganic (SiO2) materials such as glass, and have no bonding strength to the organic substrate surface of the fluorine film on the front panel of lightweight components or the glass fiber board.
[0005] Therefore, how to prepare a super-hydrophilic antifouling coating that can be combined with a lightweight component front plate is a problem that needs to be solved. Summary of the invention
[0006] The technical problem to be solved by the present invention is to provide a method for preparing a super hydrophilic antifouling coating for a lightweight component, which has better adhesion than the traditional standard component antifouling coating and solves the problem that the traditional nano coating cannot adhere to the front plate of the lightweight component.
[0007] The present invention provides a method for preparing a super-hydrophilic antifouling coating for a lightweight component, comprising the following steps: (1) placing the organosiloxane in a vacuum plasma treatment cleaning machine for plasma treatment; uniformly mixing the plasma-treated organosiloxane, acrylic monomer, and peroxide into an organic solvent to react to obtain organosilicon-modified acrylate; (2) uniformly dropping the silane coupling agent into the nano-SiO2 dispersion to react and obtain a silane-modified nano-SiO2 dispersion; (3) The above-mentioned silicone-modified acrylate, silane-modified nano-SiO2 dispersion, antistatic agent, leveling wetting agent, surfactant, and inorganic additive are sequentially added to an organic solvent and stirred, and the solvent is replaced with a mixed solvent to obtain a super hydrophilic antifouling coating for lightweight components.
[0008] Preferably, the organosiloxane in step (1) is one or more of methacryloxypropyltrimethoxysilane (MPS), polydimethylsiloxane (PDMS), and hexamethyldisiloxane (HMDS).
[0009] Preferably, the process parameters of the plasma treatment in step (1) are: the medium is an inert gas, the generating power is 10W-650W, and the gas flow rate is 20cm 3 -200cm 3 , processing time 10s-500s.
[0010] Preferably, the inert gas is one or more of helium (He), neon (Ne), and argon (Ar).
[0011] Preferably, the acrylic monomer in step (1) is one or more of butyl acrylate (BA), butyl methacrylate (MBA), acrylic acid (AA), isobornyl acrylate (IBOA), isobornyl methacrylate (IBOMA), hydroxyethyl acrylate (HEA), and hydroxyethyl methacrylate (HEMA).
[0012] Preferably, the peroxide in step (1) is one or more of dibenzoyl peroxide, dilauroyl peroxide, 1,3-bis(tert-butylperoxide isopropyl)benzene, methyl ethyl ketone peroxide, and acetylacetone peroxide.
[0013] Preferably, the mass percentage of the plasma-treated organosiloxane in step (1) is 50wt%-65wt%, the mass percentage of the acrylic acid monomer is 33wt%-48wt%, and the mass percentage of the peroxide is 0.5wt%-3wt%, based on the total mass of the organosilicon-modified acrylate reaction raw materials being 100wt%.
[0014] Preferably, the reaction temperature in step (1) is 60°C-100°C.
[0015] Preferably, the silane coupling agent in step (2) is one or more of KH-550, KH-792, KH-602, A-143, A-1310, and KH-560.
[0016] Preferably, the nano-SiO2 dispersion in step (2) is prepared by a sol-gel method, and has a particle size of 10 nm-30 nm.
[0017] Preferably, the mass percentage of the silane coupling agent in the nano-SiO2 dispersion in step (2) is 1wt%-3wt%.
[0018] Preferably, the reaction temperature in step (2) is 150°C-200°C.
[0019] Preferably, the antistatic agent in step (3) is one or more of KOELIQtm IL-P14, IL-AP8, IL-OH9, Irgastat p18-FCA, and 3M FC 4400.
[0020] Preferably, the leveling wetting agent in step (3) is one or more of AFCONA 3590, AFCONA 3779, AFCONA3280, AFCONA 3580, BYK 333, BYK 222SN, BYK 9076, TEGO 2100, and TEGO 4100.
[0021] Preferably, the surfactant in step (3) is one or more of tallow amine polyoxyethylene ether, ethoxylated coconut oil alkylamine, DOWFAX™ 20A612, AEO-9, AP 470Z, and SAFOL EN 90.
[0022] Preferably, the inorganic auxiliary agent in step (3) is one or more of CAB-O-SIL LM-150, CAB-O-SIL EH-5, CAB-O-SIL M5, AEROSIL 200, AEROSIL 300, AEROSIL 380F, and AEROSIL R202.
[0023] Preferably, in the step (3), the mass percentage of the organosilicon-modified acrylate is 10wt%-27wt%, the mass percentage of the silane-modified nano-SiO2 dispersion is 70wt%-88wt%, the mass percentage of the antistatic agent is 0.5wt%-3wt%, the mass percentage of the leveling wetting agent is 0.3wt%-1wt%, the mass percentage of the surfactant is 0.5wt%-3wt%, and the mass percentage of the inorganic additive is 0.5wt%-3wt%, based on the total mass of the raw materials of the super-hydrophilic antifouling coating for lightweight components being 100wt%.
[0024] Preferably, the organic solvent in steps (1) and (3) is tetrahydrofuran.
[0025] Preferably, the mixed solvent in step (3) is anhydrous ethanol / isopropanol / propylene glycol methyl ether / propylene glycol butyl ether / water mixed in any proportion.
[0026] Preferably, the solid content of the super hydrophilic antifouling coating for lightweight components obtained in step (3) is 5wt%-10wt%, based on the total mass of the super hydrophilic antifouling coating for lightweight components as 100wt%.
[0027] The present invention also provides a lightweight antifouling photovoltaic component, which is obtained by coating the lightweight component with a super-hydrophilic antifouling coating on the surface of the front plate of the lightweight component and then curing the coating.
[0028] Preferably, the coating is applied by one or more of roller coating, shower coating, electrostatic spray coating and scraper coating; the curing temperature is 60-100° C., and the curing time is 5-15 min.
[0029] Preferably, the lightweight anti-fouling photovoltaic module comprises a lightweight module front plate, an adhesive film, a battery cell, an adhesive film, and a back plate which are sequentially arranged with a coating.
[0030] Beneficial Effects (1) The super-hydrophilic antifouling coating prepared by the present invention has better adhesion than the traditional standard component antifouling coating, which solves the problem that the traditional nano coating cannot adhere to the front plate of the lightweight component.
[0031] (2) The present invention synthesizes a super-hydrophilic-antistatic polyhydroxy coating structure so that the coating can be fully spread on the surface of the front plate of the lightweight component to isolate the component from pollutants. At the same time, the excellent antistatic property can further reduce the accumulation of dust.
[0032] (3) The synthesized organosilicon-modified acrylate in the coating structure of the present invention gives the coating excellent weather resistance and coating adhesion. Compared with traditional nano coatings that fail in less than half a year and need to be re-coated, the coating of the present invention can last longer. DETAILED DESCRIPTION
[0033] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.
[0034] Example 1 Put methacryloxypropyltrimethoxysilane (MPS) into a vacuum plasma treatment cleaning machine. The cleaning medium is argon (Ar), the power is 300w, and the gas flow rate is 100cm 3 , process MPS for 100s.
[0035] Plasma-treated MPS (50 wt %), isobornyl acrylate (IBOA) (15 wt %), isobornyl methacrylate (IBOMA) (15 wt %), butyl acrylate (BA) (18 wt %), and dibenzoyl peroxide (2 wt %) were uniformly mixed in tetrahydrofuran (THF), reacted at 60 ° C, and the solvent was precipitated to obtain silicone-modified acrylate.
[0036] The silane coupling agent KH-602 (the mass percentage of the silane coupling agent KH-602 in the nano-SiO2 dispersion is 1wt%) is evenly dropped into the nano-SiO2 (particle size 10nm) dispersion, and reacted at 150°C for 30min to obtain a silane-modified nano-SiO2 dispersion.
[0037] Silicone-modified acrylate (27wt%), silane-modified nano-SiO2 dispersion (70wt%), antistatic agent IL-AP8 (1.5wt%), leveling wetting agent AFCONA 3590 (0.5wt%), surfactant tallow amine polyoxyethylene ether (0.5wt%), and inorganic additive CAB-O-SIL LM-150 (0.5wt%) were slowly added to THF in sequence, and stirred at a high speed of 1500 rpm. THF was replaced with a mixed solvent of anhydrous ethanol: isopropanol: propylene glycol methyl ether: propylene glycol butyl ether: water in a mass ratio of 2:1:1:2:2 by a solvent replacement method to obtain a super hydrophilic antifouling coating (solid content 5wt%) for lightweight components.
[0038] The coating was applied on the surface of the lightweight component by electrostatic spraying, with a curing temperature of 60°C and a curing time of 5 minutes to obtain a lightweight anti-fouling photovoltaic component.
[0039] Example 2 Put methacryloxypropyltrimethoxysilane (MPS) into a vacuum plasma treatment cleaning machine. The cleaning medium is argon (Ar), the power is 300w, and the gas flow rate is 100cm 3 , process MPS for 100s.
[0040] Plasma-treated MPS (60 wt %), isobornyl acrylate (IBOA) (15 wt %), isobornyl methacrylate (IBOMA) (15 wt %), butyl acrylate (BA) (9.5 wt %), and dibenzoyl peroxide (0.5 wt %) were uniformly mixed in tetrahydrofuran (THF), reacted at 60 ° C, and the solvent was precipitated to obtain silicone-modified acrylate.
[0041] The silane coupling agent KH-602 (the mass percentage of the silane coupling agent KH-602 in the nano-SiO2 dispersion is 1wt%) is evenly dropped into the nano-SiO2 (particle size 10nm) dispersion, and reacted at 150°C for 30min to obtain a silane-modified nano-SiO2 dispersion.
[0042] Silicone-modified acrylate (27wt%), silane-modified nano-SiO2 dispersion (70wt%), antistatic agent IL-AP8 (1.5wt%), leveling wetting agent AFCONA 3590 (0.5wt%), surfactant tallow amine polyoxyethylene ether (0.5wt%), and inorganic additive CAB-O-SIL LM-150 (0.5wt%) were slowly added to THF in sequence, and stirred at a high speed of 1500 rpm. THF was replaced with a mixed solvent of anhydrous ethanol: isopropanol: propylene glycol methyl ether: propylene glycol butyl ether: water in a mass ratio of 2:1:1:2:2 by a solvent replacement method to obtain a super hydrophilic antifouling coating (solid content 5wt%) for lightweight components.
[0043] The coating was applied on the surface of the lightweight component by electrostatic spraying, with a curing temperature of 60°C and a curing time of 5 minutes to obtain a lightweight anti-fouling photovoltaic component.
[0044] Example 3 Put methacryloxypropyltrimethoxysilane (MPS) into a vacuum plasma treatment cleaning machine. The cleaning medium is argon (Ar), the power is 300w, and the gas flow rate is 100cm 3 , process MPS for 100s.
[0045] Plasma-treated MPS (65 wt %), isobornyl acrylate (IBOA) (10 wt %), isobornyl methacrylate (IBOMA) (10 wt %), butyl acrylate (BA) (14.5 wt %), and dibenzoyl peroxide (0.5 wt %) were uniformly mixed in tetrahydrofuran (THF), reacted at 60 ° C, and the solvent was precipitated to obtain silicone-modified acrylate.
[0046] The silane coupling agent KH-602 (the mass percentage of the silane coupling agent KH-602 in the nano-SiO2 dispersion is 1wt%) is evenly dropped into the nano-SiO2 (particle size 10nm) dispersion, and reacted at 150°C for 30min to obtain a silane-modified nano-SiO2 dispersion.
[0047] Silicone-modified acrylate (27wt%), silane-modified nano-SiO2 dispersion (70wt%), antistatic agent IL-AP8 (1.5wt%), leveling wetting agent AFCONA 3590 (0.5wt%), surfactant tallow amine polyoxyethylene ether (0.5wt%), and inorganic additive CAB-O-SIL LM-150 (0.5wt%) were slowly added to THF in sequence, and stirred at a high speed of 1500 rpm. THF was replaced with a mixed solvent of anhydrous ethanol: isopropanol: propylene glycol methyl ether: propylene glycol butyl ether: water in a mass ratio of 2:1:1:2:2 by a solvent replacement method to obtain a super hydrophilic antifouling coating (solid content 5wt%) for lightweight components.
[0048] The coating was applied on the surface of the lightweight component by electrostatic spraying, with a curing temperature of 60°C and a curing time of 5 minutes to obtain a lightweight anti-fouling photovoltaic component.
[0049] Example 4
[0050] Except that the organosiloxane MPS is replaced by polydimethylsiloxane (PDMS), the remaining steps are the same as those in Example 1.
[0051] Example 5
[0052] Except that the organosiloxane MPS is replaced by hexamethyldisiloxane (HMDS), the remaining steps are the same as those in Example 1.
[0053] Example 6
[0054] The remaining steps are the same as those in Example 1 except that the acrylic acid monomer is replaced by hydroxyethyl methacrylate (HEMA) (15 wt %), butyl methacrylate (MBA) (15 wt %), and isobornyl methacrylate (IBOMA) (18 wt %).
[0055] Example 7
[0056] Except that the acrylic acid monomer is replaced by acrylic acid (AA) (15 wt %), butyl acrylate (BA) (15 wt %), and isobornyl acrylate (IBOA) (18 wt %), the remaining steps are the same as those in Example 1.
[0057] Example 8
[0058] Except that the SiO2 particle size is replaced with 20 nm, the remaining steps are the same as those in Example 1.
[0059] Example 9 The first three steps are the same as in Example 1.
[0060] Silicone-modified acrylate (17wt%), silane-modified nano-SiO2 dispersion (80wt%), antistatic agent IL-AP8 (1.5wt%), leveling wetting agent AFCONA 3590 (0.5wt%), surfactant tallow amine polyoxyethylene ether (0.5wt%), and inorganic additive CAB-O-SIL LM-150 (0.5wt%) were slowly added to THF in sequence, and stirred at a high speed of 1500 rpm. THF was replaced with a mixed solvent of anhydrous ethanol: isopropanol: propylene glycol methyl ether: propylene glycol butyl ether: water in a mass ratio of 2:1:1:2:2 by a solvent replacement method to obtain a super hydrophilic antifouling coating (solid content 5wt%) for lightweight components.
[0061] The coating was applied on the surface of the lightweight component by electrostatic spraying, with a curing temperature of 60°C and a curing time of 5 minutes to obtain a lightweight anti-fouling photovoltaic component.
[0062] Example 10 The first three steps are the same as in Example 1.
[0063] Silicone-modified acrylate (10wt%), silane-modified nano-SiO2 dispersion (88wt%), antistatic agent IL-AP8 (0.5wt%), leveling wetting agent AFCONA 3590 (0.5wt%), surfactant tallow amine polyoxyethylene ether (0.5wt%), and inorganic additive CAB-O-SIL LM-150 (0.5wt%) were slowly added to THF in sequence, and stirred at a high speed of 1500 rpm. THF was replaced with a mixed solvent of anhydrous ethanol: isopropanol: propylene glycol methyl ether: propylene glycol butyl ether: water in a mass ratio of 2:1:1:2:2 by a solvent replacement method to obtain a super hydrophilic antifouling coating (solid content 5wt%) for lightweight components.
[0064] The coating was applied on the surface of the lightweight component by electrostatic spraying, with a curing temperature of 60°C and a curing time of 5 minutes to obtain a lightweight anti-fouling photovoltaic component.
[0065] Embodiment 11 The first three steps are the same as in Example 1.
[0066] Silicone-modified acrylate (25wt%), modified nano-SiO2 dispersion (70wt%), antistatic agent IL-AP8 (1.5wt%), leveling wetting agent AFCONA 3590 (0.5wt%), surfactant tallow amine polyoxyethylene ether (0.5wt%) and inorganic additive CAB-O-SIL LM-150 (2.5wt%) were slowly added to THF in sequence, and stirred at a high speed of 1500 rpm. THF was replaced with a mixed solvent of anhydrous ethanol: isopropanol: propylene glycol methyl ether: propylene glycol butyl ether: water in a mass ratio of 2:1:1:2:2 by a solvent replacement method to obtain a super hydrophilic antifouling coating (solid content 5wt%) for lightweight components.
[0067] The coating was applied on the surface of the lightweight component by electrostatic spraying, with a curing temperature of 60°C and a curing time of 5 minutes to obtain a lightweight anti-fouling photovoltaic component.
[0068] Example 12
[0069] Except that the antistatic agent was replaced by Irgastat p18-FCA, the rest was the same as Example 1.
[0070] Example 13
[0071] Except that the leveling wetting agent is replaced by BYK 222SN, the rest is the same as Example 1.
[0072] Embodiment 14
[0073] Except that the surfactant was replaced by DOWFAX™ 20A612, the rest was the same as in Example 1.
[0074] Embodiment 15
[0075] Except that the inorganic auxiliary agent is replaced by AEROSIL 300, the rest is the same as Example 1.
[0076] Example 16
[0077] The method is the same as Example 1 except that the mixed solvent ratio is replaced by anhydrous ethanol: isopropanol: propylene glycol methyl ether: propylene glycol butyl ether: water in a mass ratio of 1:2:3:1:1.
[0078] Comparative Example 1 Methacryloyloxypropyltrimethoxysilane (MPS) (50wt%), isobornyl acrylate (IBOA) (15wt%), isobornyl methacrylate (IBOMA) (15wt%), butyl acrylate (BA) (18wt%), and dibenzoyl peroxide (2wt%) were uniformly mixed in tetrahydrofuran (THF), reacted at 60°C, and the solvent was precipitated to obtain silicone-modified acrylate.
[0079] The silane coupling agent KH-602 (the mass percentage of the silane coupling agent KH-602 in the nano-SiO2 dispersion is 1wt%) is evenly dropped into the nano-SiO2 (particle size 10nm) dispersion, and reacted at 150°C for 30min to obtain a silane-modified nano-SiO2 dispersion.
[0080] Silicone-modified acrylate (27wt%), modified nano-SiO2 dispersion (70wt%), antistatic agent IL-AP8 (2.5wt%) and leveling wetting agent AFCONA 3590 (0.5wt%) were slowly added to THF in sequence, and stirred at a high speed of 1500 rpm. THF was replaced with a mixed solvent of anhydrous ethanol: isopropanol: propylene glycol methyl ether: propylene glycol butyl ether: water in a mass ratio of 2:1:1:2:2 by a solvent replacement method to obtain an antifouling coating (solid content 5wt%) for lightweight components.
[0081] The coating was applied on the surface of the lightweight component by electrostatic spraying, with a curing temperature of 60°C and a curing time of 5 minutes to obtain a lightweight anti-fouling photovoltaic component.
[0082] Comparative Example 2 Silane-modified nano-SiO2 dispersion (97wt%), antistatic agent IL-AP8 (2.5wt%) and leveling wetting agent AFCONA3590 (0.5wt%) were slowly added to THF in sequence, and stirred at a high speed of 1500 rpm. THF was replaced with a mixed solvent of anhydrous ethanol: isopropanol: propylene glycol methyl ether: propylene glycol butyl ether: water in a mass ratio of 2:1:1:2:2 by the solvent replacement method to obtain a super hydrophilic antifouling coating (solid content 5wt%) for lightweight components.
[0083] The coating was applied on the surface of the lightweight component by electrostatic spraying, with a curing temperature of 60°C and a curing time of 5 minutes to obtain a lightweight photovoltaic component.
[0084] Comparative Example 3 Put methacryloxypropyltrimethoxysilane (MPS) into a vacuum plasma treatment cleaning machine. The cleaning medium is argon (Ar), the power is 300w, and the gas flow rate is 100cm 3 , process MPS for 100s.
[0085] Plasma-treated MPS (50 wt %), isobornyl acrylate (IBOA) (15 wt %), isobornyl methacrylate (IBOMA) (15 wt %), butyl acrylate (BA) (18 wt %), and dibenzoyl peroxide (2 wt %) were uniformly mixed in tetrahydrofuran (THF), reacted at 60 ° C, and the solvent was precipitated to obtain silicone-modified acrylate.
[0086] The silane coupling agent KH-602 (the mass percentage of the silane coupling agent KH-602 in the nano-SiO2 dispersion is 1wt%) is evenly dropped into the nano-SiO2 (particle size 10nm) dispersion, and reacted at 150°C for 30min to obtain a silane-modified nano-SiO2 dispersion.
[0087] Silicone-modified acrylate (27wt%), modified nano-SiO2 dispersion (70wt%), leveling wetting agent AFCONA3590 (1wt%), surfactant tallow amine polyoxyethylene ether (1wt%) and inorganic additive CAB-O-SIL LM-150 (1wt%) were slowly added to THF in sequence, and stirred at a high speed of 1500 rpm. THF was replaced with a mixed solvent of anhydrous ethanol: isopropanol: propylene glycol methyl ether: propylene glycol butyl ether: water in a mass ratio of 2:1:1:2:2 by a solvent replacement method to obtain a super hydrophilic antifouling coating (solid content 5wt%) for lightweight components.
[0088] The coating was applied on the surface of the lightweight component by electrostatic spraying, with a curing temperature of 60°C and a curing time of 5 minutes to obtain a lightweight anti-fouling photovoltaic component.
[0089] Comparative Example 4 The first three steps are the same as in Comparative Example 3.
[0090] Silicone-modified acrylate (27wt%), modified nano-SiO2 dispersion (70wt%), antistatic agent IL-AP8 (1.5wt%), leveling wetting agent AFCONA 3590 (1wt%) and inorganic additive CAB-O-SIL LM-150 (0.5wt%) were slowly added to THF in sequence, and stirred at a high speed of 1500 rpm. THF was replaced with a mixed solvent of anhydrous ethanol: isopropanol: propylene glycol methyl ether: propylene glycol butyl ether: water in a mass ratio of 2:1:1:2:2 by a solvent replacement method to obtain a super hydrophilic antifouling coating (solid content 5wt%) for lightweight components.
[0091] The coating was applied on the surface of the lightweight component by electrostatic spraying, with a curing temperature of 60°C and a curing time of 5 minutes to obtain a lightweight anti-fouling photovoltaic component.
[0092] Comparative Example 5 The first three steps are the same as in Comparative Example 3.
[0093] Silicone-modified acrylate (27wt%), modified nano-SiO2 dispersion (70wt%), antistatic agent IL-AP8 (1.5wt%), leveling wetting agent AFCONA 3590 (1wt%) and surfactant tallow amine polyoxyethylene ether (0.5wt%) were slowly added to THF in sequence, and stirred at a high speed of 1500 rpm. THF was replaced with a mixed solvent of anhydrous ethanol: isopropanol: propylene glycol methyl ether: propylene glycol butyl ether: water in a mass ratio of 2:1:1:2:2 by a solvent replacement method to obtain a super hydrophilic antifouling coating (solid content 5wt%) for lightweight components.
[0094] The coating was applied on the surface of the lightweight component by electrostatic spraying, with a curing temperature of 60°C and a curing time of 5 minutes to obtain a lightweight anti-fouling photovoltaic component.
[0095] Comparative Example 6 The commercial antifouling coating is from Guangzhou Sysmec, brand: YCP0051KT, which is a hydrophobic and oleophobic coating with reduced reflection and increased transmittance.
[0096] The performance test method of the antifouling coating after being coated on the front plate of the lightweight component is as follows: Contact angle: GB / T30693-2014; Yellowing value: GB / T 39822-2021; Module power: IEC 61215-2-2021; Coating adhesion: GB / T 9286-1998; the evaluation criteria for levels 0-5 are shown in this test standard; Coating wear-resistant pencil hardness: GB / T 6739-2022; The evaluation criteria of 0-5 levels are shown in this test standard. The pencil hardness here is used to detect the level of coating hardness resistance to slipping, and the wear resistance replaces the uncoated wear-resistant pencil hardness. Among them, DH refers to the aging test hours of the components under the conditions of 85°C and 85% ambient humidity, and DH1000 means 1000 hours.
[0097] The performance test results are shown in Tables 1 to 4.
[0098] Table 1 Test results of lightweight anti-fouling photovoltaic modules
[0099] Table 2 Test results of lightweight anti-fouling photovoltaic modules
[0100] Table 3 Test results of lightweight anti-fouling photovoltaic modules
[0101] Table 4 Test results of lightweight anti-fouling photovoltaic modules
[0102] As can be seen from Tables 1 to 4 above, the super-hydrophilic antifouling coatings and lightweight antifouling components prepared in Examples 1-16 have obvious adhesion and wear resistance, and the component gain has no obvious attenuation after aging, yellowing is small, and the weather resistance is excellent. In Comparative Example 1, the organic siloxane is not treated, and the hydrophilicity deteriorates, resulting in a different synthetic structure and poor component gain. Comparative Example 2 only uses modified nano-SiO2 to disperse and prepare the coating, and the adhesion is poor. After aging, the coating falls off completely. Comparative Example 3 does not add an antistatic agent, and the component power gain deteriorates after aging, indicating that the surface pollution of the component is aggravated. Comparative Example 4 does not add a surfactant, and the hydrophilicity and dispersibility after aging deteriorate, and the component gain deteriorates. In Comparative Example 5, no inorganic additive is added, the coating thixotropy and strength deteriorate, and the component power gain deteriorates after aging. Comparative Example 6 uses a traditional glass coating, which is applied on the front plate of the lightweight component with basically no adhesion.
[0103] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.
[0104] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.
Claims
1. A method for preparing a super hydrophilic antifouling coating for a lightweight component, comprising the following steps: (1) placing the organosiloxane in a vacuum plasma treatment cleaning machine for plasma treatment; uniformly mixing the plasma-treated organosiloxane, acrylic monomer, and peroxide into an organic solvent to react to obtain organosilicon-modified acrylate; wherein: The mass percentage of the plasma-treated organosiloxane is 50wt%-65wt%, the mass percentage of the acrylic monomer is 33wt%-48wt%, and the mass percentage of the peroxide is 0.5wt%-3wt%, based on the total mass of the organosilicon-modified acrylate reaction raw materials being 100wt%; (2) uniformly dropping the silane coupling agent into the nano-SiO2 dispersion to react and obtain a silane-modified nano-SiO2 dispersion; (3) The above-mentioned organosilicon-modified acrylate, silane-modified nano-SiO2 dispersion, antistatic agent, leveling wetting agent, surfactant, and inorganic additive are sequentially added to an organic solvent and stirred, and the solvent is replaced with a mixed solvent to obtain a super hydrophilic antifouling coating for lightweight components; wherein the mass percentage of the organosilicon-modified acrylate is 10wt%-27wt%, the mass percentage of the silane-modified nano-SiO2 dispersion is 70wt%-88wt%, the mass percentage of the antistatic agent is 0.5wt%-3wt%, the mass percentage of the leveling wetting agent is 0.3wt%-1wt%, the mass percentage of the surfactant is 0.5wt%-3wt%, and the mass percentage of the inorganic additive is 0.5wt%-3wt%, based on the total mass of the raw materials of the super hydrophilic antifouling coating for lightweight components as 100wt%; the antistatic agent is KOELIQtm IL-P14, IL-AP8, IL-OH9, Irgastat p18-FCA, 3M The surfactant is one or more of tallow amine polyoxyethylene ether, ethoxylated coconut oil alkylamine, DOWFAX™20A612, AEO-9, AP 470Z, and SAFOL EN 90; the inorganic auxiliary agent is one or more of CAB-O-SIL LM-150, CAB-O-SIL EH-5, CAB-O-SIL M5, AEROSIL 200, AEROSIL 300, AEROSIL 380F, and AEROSILR202.
2. The preparation method according to claim 1, characterized in that: The organosiloxane in step (1) is one or more of methacryloxypropyltrimethoxysilane, polydimethylsiloxane, and hexamethyldisiloxane.
3. The preparation method according to claim 1, characterized in that: The process parameters of the plasma treatment in step (1) are: the medium is an inert gas, the generating power is 10W-650W, and the gas flow rate is 20cm 3 -200cm 3 , processing time 10s-500s.
4. The preparation method according to claim 1, characterized in that: The acrylic monomer in step (1) is one or more of butyl acrylate, butyl methacrylate, acrylic acid, isobornyl acrylate, isobornyl methacrylate, hydroxyethyl acrylate, and hydroxyethyl methacrylate; the peroxide is one or more of dibenzoyl peroxide, dilauroyl peroxide, 1,3-bis(tert-butylperoxyisopropyl)benzene, methyl ethyl ketone peroxide, and acetylacetone peroxide.
5. The preparation method according to claim 1, characterized in that: The mass percentage of the silane coupling agent in the nano-SiO2 dispersion in step (2) is 1wt%-3wt%.
6. The preparation method according to claim 1, characterized in that: The leveling wetting agent in step (3) is one or more of AFCONA 3590, AFCONA 3779, AFCONA 3280, AFCONA 3580, BYK 333, BYK 222SN, BYK 9076, TEGO 2100, and TEGO 4100.
7. The preparation method according to claim 1, characterized in that: The organic solvent in steps (1) and (3) is tetrahydrofuran.
8. The preparation method according to claim 1, characterized in that: The solid content of the super hydrophilic antifouling coating for lightweight components obtained in step (3) is 5wt%-10wt%, based on the total mass of the super hydrophilic antifouling coating for lightweight components being 100wt%.
Citation Information
Patent Citations
Preparation method for super-hydrophilic organic silicon coating
CN103881515A
Super-hydrophilic, self-cleaning and antifogging coating and preparation method thereof
CN107227050A
Preparation method of water-based normal-temperature self-crosslinking super-hydrophilic antifogging coating
CN109868025A
Organic-inorganic hybrid anti-fog coating and preparation method thereof
CN111574899A
Super-hydrophilic antifogging coating and preparation method thereof
CN113897135A
Cited By
Photovoltaic light transparent front plate based on organic-inorganic hybrid material and preparation method thereof
CN120988416A